Performance Analysis of MQTT Protocol in IoT Environments: Impact of Payload Size and QoS on Key Metrics - Hintaw, Ahmed J (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
The advancement of Internet of Things (IoT) technology represents the transformative opportunity and already overcomes this limiting factor, utilizing lightweight communication protocols to minimize overhead compared to traditional internet systems. MQTT is one of the popular and efficient protocol used in IoT to exchange data. In this work, we investigate the MQTT behavior in given IoT scenarios by considering payload sizes (5 MB, 10 MB,15 MB, and 20 MB) and QoS levels as influencing factors for performance metrics such as throughput, execution time, traffic overhead, and latency. Testbed experiments on a Raspberry Pi 3 indicate that processing time scales with payload size and QoS-2 (highest reliability) introduces overhead up to an order-of-magnitude. For bigger payloads, throughput increases with QoS-0 (lowest reliability) delivering the highest throughput rates, while latency increases with both payload size and QoS level. The results provide important insight on how to efficiently improve the reliability of MQTT, as it evidences the possible trade-offs between both categories.